2009
DOI: 10.1007/s00277-009-0697-7
|View full text |Cite
|
Sign up to set email alerts
|

Hemin-induced suicidal erythrocyte death

Abstract: Several diseases, such as malaria, sickle cell disease, and ischemia/reperfusion may cause excessive formation of hemin, which may in turn trigger hemolysis. A variety of drugs and diseases leading to hemolysis triggers suicidal erythrocyte death or eryptosis, i.e., cell membrane scrambling and cell shrinkage. Eryptosis is elicited by increased cytosolic Ca 2+ activity and by ceramide. The present study explored whether hemin stimulates eryptosis. Cell membrane scrambling was estimated from annexin Vbinding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 74 publications
2
25
1
1
Order By: Relevance
“…However, it was reported that 4% of RBC were hemolyzed 48 hrs after the incubation with hemin at C = 10 μM8. In the latter experiments RBC were incubated in a Ringer solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was reported that 4% of RBC were hemolyzed 48 hrs after the incubation with hemin at C = 10 μM8. In the latter experiments RBC were incubated in a Ringer solution.…”
Section: Discussionmentioning
confidence: 99%
“…This was proved by the electrophoresis and electron spin resonance methods5. A variety of disorders may lead to a formation of hemin, which in turn causes hemolysis89.…”
mentioning
confidence: 98%
“…malaria [49][50][51][52][53], Wilson's disease [54] and possibly metabolic syndrome [55]. Eryptosis is further stimulated by a wide variety of small molecules [56][57][58][59][60][61][62][63]. The proeryptotic effect of dicoumarol could be compounded in those clinical conditions and in the presence of those chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical conditions associated with anemia have been shown to be paralleled by accelerated eryptosis [16], such as iron deficiency [1], phosphate depletion [17], Hemolytic Uremic Syndrome [18], sepsis [19], malaria [20][21][22], or Wilson's disease [23]. Moreover, eryptosis may be triggered by a wide variety of endogeneous substances and xenobiotics, such as antiA IgG antibodies [24], cordycepin [25], hemin [26], amiodarone [27], methylglyoxal [28], amyloid peptides [29], anandamide [30], lipopetides [31] retinoic acid [32], paclitaxel [33], amantadine [34], chlorpromazine [35], ciglitazone [36]. cyclosporine [37], Bay-5884 [38], curcumin [39], valinomycin [40], listeriolysin [41], aluminium [42], bismuth [43], mercury [44], copper [23], cadmium [45], selenium [46], vanadate [47], gold [48] and arsenic [49].…”
Section: Introductionmentioning
confidence: 99%